Implementasi Fuzzy Analytic Network Process Untuk Menentukan Prioritas Perbaikan Safety Performance pada Perusahaan Manufaktur - Nuruddin Hamid; Adithya Sudiarno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Workplace safety is a top priority for business continuity, particularly in industries with high accident risks. Every company is responsible for ensuring a safe work environment for all employees. Failing to implement an effective safety system can be detrimental, impacting not only worker safety and health but also the company's reputation. Field data from PT. X reveals anomalies in safety performance over the last five semesters (2022–2024), as evidenced by unmet zero accident Key performance indicator (KPI) targets. This study aims to establish priorities for safety performance improvement based on criteria such as safety leadership, safety participation, safety climate, and safety knowledge, and to evaluate solutions for employees, outsourcing, or contractors to achieve zero accident KPI or improved safety performance. The Fuzzy Analytic Network Process (FANP) approach is utilized to identify prioritized alternative solutions for enhancing safety performance. The findings of this study reveal that the highest weighted criterion for safety performance improvement is safety leadership (0.123962), followed by safety knowledge (0.110077), safety participation (0.097962), and safety climate (0.067998). In terms of the worker categories targeted for improvement, employees—who are the primary resources responsible for operations and must possess high competence and motivation in implementing safety standards—received the highest weight (0.146306), followed closely by outsourcing workers (0.145482) and contractors (0.108211). The application of the fuzzy ANP method produces prioritized safety performance improvements based on multiple criteria, allowing these recommendations to be utilized by PT. X management for effective resource management. Furthermore, it is recommended to develop an action plan and monitor gaps after implementing the recommendations.